The pectoral girdle of StW 573 ('Little Foot') and its implications for shoulder evolution in the Hominina. Issue 158 (September 2021) - Carlson, Kristian J.; Green, David J.; Jashashvili, Tea; Pickering, Travis R.; Heaton, Jason L.; Beaudet, Amélie; Stratford, Dominic; Crompton, Robin; Kuman, Kathleen; Bruxelles, Laurent; Clarke, Ronald J.
Abstract: The ca. 3.67 Ma adult skeleton known as 'Little Foot' (StW 573), recovered from Sterkfontein Member 2 breccia in the Silberberg Grotto, is remarkable for its morphology and completeness. Preservation of clavicles and scapulae, including essentially complete right-side elements, offers opportunities to assess morphological and functional aspects of a nearly complete Australopithecus pectoral girdle. Here we describe the StW 573 pectoral girdle and offer quantitative comparisons to those of extant hominoids and selected homininans. The StW 573 pectoral girdle combines features intermediate between those of humans and other apes: a long and curved clavicle, suggesting a relatively dorsally positioned scapula; an enlarged and uniquely proportioned supraspinous fossa; a relatively cranially oriented glenoid fossa; and ape-like reinforcement of the axillary margin by a stout ventral bar. StW 573 scapulae are as follows: smaller than those of some homininans (i.e., KSD-VP-1/1 and KNM-ER 47000A), larger than others (i.e., A.L. 288-1, Sts 7, and MH2), and most similar in size to another australopith from Sterkfontein, StW 431. Moreover, StW 573 and StW 431 exhibit similar structural features along their axillary margins and inferior angles. As the StW 573 pectoral girdle (e.g., scapular configuration) has a greater affinity to that of apes— Gorilla in particular—rather than modern humans, we suggest that the StW 573 morphological pattern appears to reflect adaptations to arboreal behaviors, especially those with the hand positioned above the head, more than human-like manipulatory capabilities. When compared with less complete pectoral girdles from middle/late Miocene apes and that of the penecontemporaneous KSD-VP-1/1 ( Australopithecus afarensis ), and mindful of consensus views on the adaptiveness of arboreal positional behaviors soliciting abducted glenohumeral joints in early Pliocene taxa, we propose that the StW 573 pectoral girdle is a reasonable model for hypothesizing pectoral girdle configuration of the crown hominin last common ancestor.